Characteristics of Rat Lumbar Vertebral Body Bone Mineral Density and Differential Segmental Responses to Sex Hormone Deficiency： a Clinical Multidetector Computed Tomography Study - DENG, Min; WANG, Yi Xiang; GRIFFITH, James F.; LU, Gang; AHUJA, Anil T; POON, Wai S (Biomedical and environmental sciences, 2012)
Objective To investigate sex hormone deficiency related osteoporosis and efficacy of different therapies. Methods Orchiectomized and ovariectomized rat models are used to investigate sex hormone deficiency related osteoporosis and efficacy of different therapies. A rat vertebral body can be longitudinally divided into central portion, which contain more trabecular bone, and para-endplate portions which contain more compact bone. In matured male and female Wistar and Sprague-Dawley rat lumbar spines, we investigated baseline bone mineral density （BMD） characteristics and the differential segmental responses in bone loss within the lumbar vertebral body post gonadal surgery with clinical multidetector computed tomography. Results Para-endplate sections had a higher BMD than central sections. The cephalad para-endplate sections had a higher BMD than the caudad para-endplate sections. Eight weeks after gonadal removal, there was more bone loss in central sections than para-endplate sections. The relative difference of bone loss between para-endplate and central sections was more apparent in male rats than in female rats. There was more bone loss in caudad sections than cephalad sections; this lead to a further increase of BMD difference between caudad para-endplate sections and cephalad para-endplate sections post gonadal surgery. Conclusion The approach described in this study provided a consistent way to study BMD change within predominantly compact bone portion and trabecular bone portion of the vertebral body.